Kajian Stilistika Teks Lagu dalam Album Untukmu Selamanya Karya Band Ungu - Lestari, Septiani; Wardiani, Ririen; Setiawan, Heru (Jurnal Bahasa dan Sastra, 2021)
This research is motivated by the interesting use of word choice or diction and figurative language used by Ungu band. For this reason, this study aims to analyze the use of diction and figurative language contained in the album Untukmu Selamanya. The method used is descriptive with a literature review design. Data are collected by using the note-taking technique. The data are analyzed by employing descriptive technique including the following steps; data selection, coding, data classification, data description, and data interpretation. The data source of this research is the three song texts on the album Untukmu Selamanya by Ungu band. The result of the analysis shows that the majority of the diction contained in the song is connotative. This is a manifestation of the song composer’s creativity when creating lyrics. Another finding is the use of figurative language, synecdoche and simile with the theme of romance and sadness.